Baboon syndrome induced by hydroxyzine - Hayet Akkari; Hichem Belhadjali; Monia Youssef; Sana Mokni; Jamelediine Zili (Wolters Kluwer Medknow Publications, 2013)
Hydroxyzine-induced drug eruptions are very rare. We report here a typical case of drug-related Baboon syndrome or symmetrical drug-related intertriginous and flexural exanthema (SDRIFE) which was induced by hydroxyzine in a 60-year-old man. The diagnosis was confirmed by positive patch and oral accidental provocation tests with hydroxyzine. Patch tests and oral provocation tests with cetirizine and levocetirizine were negative. A review of the literature identified only 17 reported cases of hydroxyzine-induced drug eruptions. To the best of our knowledge, we report here the first case of hydroxyzine-induced SDRIFE.